Interfacial Chemical and Mechanical Reactions between Tungsten-Film and Nano-Scale Colloidal Zirconia Abrasives for Chemical-Mechanical-Planarization. (18th May 2020) - Seo, Eun-Bin; Bae, Jae-Young; Kim, Sung-In; Choi, Han-Eol; Son, Young-Hye; Yun, Sang-Su; Park, Jin-Hyung; Park, Jea-Gun
Abstract : In tungsten (W) film chemical-mechanical-planarization (CMP), the chemical and mechanical reaction behaviors of the W film surface play a critical role in the CMP performance, as determined by oxidation (i.e., WO3 ), corrosion (i.e., WO4 2− ), and the electrostatic force at the interface between abrasives and the surface. Unlike a conventional catalyst (i.e., Fe(NO3 )3 ) for a Fenton reaction in a CMP slurry, a new catalyst ((i.e., potassium ferric oxalate: K3 Fe(C2 O4 )3 )) and a new nano-scale (i.e., 23 nm in diameter) abrasives (i.e., Zirconia:ZrO2 ) provides specific CMP performance behavior: the maximum W-film polishing rate and a corrosion-free surface are achieved at a specific catalyst concentration (0.03 wt%), and the number of remaining abrasives adsorbed on the W film surface after CMP decreases with increasing concentration of the K3 Fe(C2 O4 )3 . These CMP performance characteristics are associated with the following results: (i) The degrees of two different CMP mechanisms (oxidation-dominant or corrosion-dominant) determine the corrosion-free surface of W film. (ii) The dependency of the electrostatic force at the interface between abrasives and the film on the K3 Fe(C2 O4 )3 concentration determines the polishing rate. Finally, (iii) the zeta potential distribution at the interface between the abrasives and the film directly affects the number of remaining abrasives on the surface after CMP.